Implementation of Endowment as Arising of People's Economy - Darania Anisa; Adib Fachri (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
The appearance of poverty is caused by discrepancy or gap regarding to land and asset ownership in Indonesia. Rich people in Indonesia dominate almost 70 percent of land, whereas 99 percent of people acquire only 30 percents of and. In this case, the utilization of waqf/endowment land can become a solution to develop economy and poverty alleviation. The existence of the law Number 41 Year 2004 about endowment/waqf gives the juridical foundation for endowment implementation, either endowment of fixed asset and building, or form of money. Endowment implementation should encompass productivity factor ad consumptive factor in society, so it can give positive impact for public welfare.